(untitled) (Research, Society and Development, 2020)
The performance of the pedagogical professional nowadays has been going beyond the limits traditionally established by the walls of schools, going beyond these, and becoming necessary in all spaces where teaching and learning take place, whether formal or non-formal. Under this threshold, the study has as main objective to identify the knowledge that these students present about the possibilities of performance attributed to the professional trained in pedagogy. To carry out this investigation, it was methodologically defined, through the adoption of bibliographic and field research with a qualitative character. Would the young graduates of the pedagogy course have ownership over their future professional areas? In this article, it is proposed to discuss this issue, presenting in its body two sections: in the first, a literature review is made, briefly describing the origin and consolidation of the pedagogy course in Brazil and the construction of its identity. In the second section, some fragments and procedures of an interview carried out in the investigative process of the construction of a Master’s Dissertation on the choice of the pedagogy course are presented. In this regard, it is evident the lack of knowledge that they have about the spaces of performance of this education professional.